Pharmacokinetics of recombinant factor XIII at steady state in patients with congenital factor XIII A‐subunit deficiency. (25th October 2014) - Kerlin, B.; Brand, B.; Inbal, A.; Halimeh, S.; Nugent, D.; Lundblad, M.; Tehranchi, R.
Summary Background The use of monthly recombinant factor XIII (rFXIII) recently demonstrated favorable safety and efficacy for congenital FXIII A‐subunit deficiency patients aged ≥ 6 years (mentor™1 trial), although the pharmacokinetics (PK) were not fully evaluated. Objectives To comprehensively evaluate the steady‐state PK of rFXIII in patients aged ≥ 6 years with congenital FXIII A‐subunit deficiency. Patients/methods mentor™2 is an ongoing, multinational safety and efficacy trial in which patients are receiving monthly rFXIII (35 IU kg−1) for ≥ 52 weeks. For this 28‐day PK analysis, blood samples were collected immediately predosing, and 1 h, 2 h, 3, 7, 14, 21, and 28 days postdosing. FXIII activity was measured and PK parameters were calculated using non‐compartmental analysis, without prior baseline adjustment. Information regarding adverse events and bleeding was collected at each visit. Antibody assessments were performed predosing and at day 28. Results PK analysis in 23 patients revealed first‐order elimination of rFXIII with a geometric mean half‐life of 13.6 days. Mean FXIII activity was > 0.1 IU mL−1 throughout the 28‐day period, with a geometric mean peak activity of 0.87 IU mL−1 and trough of 0.16 IU mL−1. The geometric mean clearance was 0.15 mL h−1 kg−1. No bleeding episodes occurred during the PK session, and no anti‐rFXIII antibodies were detected. Peak and trough FXIII activities were constant over time, compared with previous activities (≥ 10 rFXIII doses) in the same patients. Conclusions Clearance of rFXIII is unaffected over time, and monthly prophylaxis with 35 IU kg−1 rFXIII provides FXIII activity > 0.1 IU mL−1 throughout the dosing interval in patients with congenital FXIII A‐subunit deficiency.